Síndrome de Kabuki: caracterización clínica, estudios genéticos, manejo preventivo de las complicaciones y asesoría genética (2012)
Introduction: Kabuki refers to traditional Japanese theater, and the syndrome's name comes from the similarity of the patients' facialmakeup used by these actors. Kabuki syndrome is a dismorfological pathology characterized by particular facial features including widepalpebral fissures, depressed nasal tip, arched eyebrows with the lateral one-third dispersed or sparse, and prominent ears. All thesefeatures are concomitant, with mental retardation, cardiopathies, nephropathies , among others. Due to the presence in greater orlesser number of times certain pathologies, have been divided into minor and major abnormalities. Objective: present a review of thegeneralities of Kabuki syndrome, dismorfologicas features, clinical characteristics, complications, and genetic studies to date. Methods:we used the databases PubMed and SciELO, to search for information. Results: the published studies alluding to the first cases of thesyndrome, even those published recently where MLL2 gene is identified as a possible candidate for this syndrome. Conclusions. until nowthe diagnosis is made by clinical findings, although it can detect the mutation of gene MLL2. For the diagnosis is given through the familyhistory and physical examination findings, especially the facial features, characteristic of this syndrome. Complementing the diagnosismust be carry out a preventive management of complications and to avoid potential risks, and offer the family information during geneticcounseling. (MÉD.UIS. 2011;25(1):19-27).Key Words: Kabuki Syndrome. Craniofacial anomalies. Arched eyebrows. Sparse eyebrows. Long palpebral fissures. Cleft lip/palate